Mindfulness como estratégia terapêutica para o pensamento ruminativo : uma revisão sistemática e de escopo - Souza, Landerson Carlos Martins de (2024)
Rumination, a form of perseverative cognition, is considered a crucial factor in the etiology and maintenance of depression, as it involves a constant repetition of negative thoughts, exacerbating depressive symptoms. Mindfulness is a therapy used in healthcare to reduce stress, pain, anxiety and also tinnitus. The present objective study verifies, through a scoping review and a systematic review, whether mindfulness is an effective therapy for ruminative thinking in adults, when compared to other treatments. This systematic review was designed and reported following PRISMA recommendations. An electronic search was carried out in three databases: PUBMED, Science Direct and Lilacs. The search was carried out in pairs on December 20, 2023, using the PICOS strategy: P (Population): adults with repetitive/ruminative thoughts, I (Intervention): mindfulness, C (Comparison): another form of therapy or lack of therapy, O (Outcome): improvement in rumination symptoms, and S (Type of study): any type of investigation. The selection of studies was carried out in two moments, independently, by two researchers, with discrepancies resolved by a third researcher. After selection, the articles were evaluated with the Cochrane Risk of Bias Tool 2.0 – RoB 2.0, used to evaluate evaluated clinical trials, in the context of the systematic review. Initially, 289 studies were found in the three databases searched. After removing duplicates and articles outside the PICOS strategy, 20 studies remained for reading abstracts and titles. After complete reading, 9 documents were reviewed, resulting in the exclusion of 5 articles for not meeting the PICOS criteria, leaving 4 studies for final analysis. This review concluded that mindfulness can be used as a therapy for the treatment of ruminative thinking in the adult population.